THE IMPACT OF E-QUALITY TO E-LOYALTY AND E-SATISFACTION AT ZALORA - Brenda Jacqueline (CALYPTRA, 2016)
This study aims to find out and analyze the effect of E-quality which is consists of five dimensions to E-loyalty by E-trust and E-satisfaction of Zalora company. This study used Structural Equation Modeling (SEM) with LISREL software version 8.7. Sampling technique used in this study is a non-probability sampling technique with the type of convenience sampling. This study used survey to collect data by distributing the questionnaires through online by using Google Docs. Sample of this study consisted of one hundre seventy (170) respondents .The respondents must have buy goods at Zalora and have graduated from junior high school, or the minimum age is 15. This study reveals that the E-quality is significantly and positively correlated to E-trust and E-satisfaction of Zalora company in Indonesia. Furthermore, e-trust had no significant effect to e-loyalty of Zalora company. Therefore, E-quality is the only variable that is significantly and positively correlated to E-loyalty by E-satisfaction of Zalora company in Indonesia.